1985
DOI: 10.1080/00288330.1985.9516078
|View full text |Cite
|
Sign up to set email alerts
|

Burrowing behaviour of the paddle crabOvalipes catharus(White, 1843) (Brachyura: Portunidae)

Abstract: The burrowing behaviour of Ovalipes catharus (White, 1843) is described and compared with that of some other burrowing crabs. O. catharus is a fast, back burrowing crab which makes temporary burrows in soft sand. The average time from initiation of burrowing to complete submergence was 6.5 s, there was no difference between males and females but burrowing time increased significantly with crab size. Similar morphological adaptations are required for burrowing and swimming: streamlined body shape, smooth lightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The size of the animal affects the burial time, with larger animals taking longer to bury. Ovalipes catharus of comparable size to the crabs used in the present study have similar burial times (24 s; McLay and Osborne, 1985) to those observed for C. magister (26.1 s). Although C. magister buries significantly faster than C. productus (59.5 s), it is not without cost: a much larger increase in cardiac parameters and blood flow is necessary to assist this process (McGaw, 2004).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The size of the animal affects the burial time, with larger animals taking longer to bury. Ovalipes catharus of comparable size to the crabs used in the present study have similar burial times (24 s; McLay and Osborne, 1985) to those observed for C. magister (26.1 s). Although C. magister buries significantly faster than C. productus (59.5 s), it is not without cost: a much larger increase in cardiac parameters and blood flow is necessary to assist this process (McGaw, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…The burying style exhibited by Cancer productus is similar to that reported for the paddle crab, Ovalipes catharus, where the legs pull the animal down and a final push with the chelae submerges the animal in the sediment (McLay and Osborne, 1985). Unlike C. productus, Cancer magister excavates the sand with its legs.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Caine (1974) andMcLay &Osborne (1985) have provlded evidence that Ovalipes spp. are both n~orphologically and behaviorally adapted to a burrowing existence.…”
Section: Discussionmentioning
confidence: 99%